Idea evaluation as a design process: understanding how experts develop ideas and manage fixations. (24th April 2023) - Boudier, Justine; Sukhov, Alexandre; Netz, Johan; Le Masson, Pascal; Weil, Benoit
Abstract: Idea evaluation is used to identify and select ideas for development as future innovations. However, approaching idea evaluation as a decision gate can limit the role of the person evaluating ideas, create fixation bias, and underutilise the person's creative potential. Although studies show that during evaluation experts are able to engage in design activities, it is still not clear how they design and develop ideas. The aim of this study was to understand how experts develop ideas during evaluation. Using the think-aloud technique, we identify different ways in which experts develop ideas. Specifically, we show how experts transform initial idea concepts using iterative steps of elaboration and transformation of different idea components. Then, relying on concept-knowledge theory (C-K theory), we identify six types of reasoning that the experts use during idea evaluation. This helps us to distinguish between three different roles that experts can move between during evaluation: gatekeeper, designer managing fixation, and designer managing defixation. These findings suggest that there is value in viewing idea evaluation as a design process because it allows us to identify and leverage the experts' knowledge and creativity to a fuller extent.